Complete characterization and comparative analysis of the mitochondrial genome of Indian tasar silkworm Antheraea mylitta (Lepidoptera: Saturniidae) and phylogenetic implications - Indumathi Kamatchi Balakrishnan; Himanshu Dubey; Rajal Debnath; Gangavarapu Subrahmanyam; P. Kallare Arunkumar; Jay Prakash Pandey; Kangayam M. Ponnuvel; Vankadara Sivaprasad; Kutala Sathyanarayana (Journal of Asia-Pacific Biodiversity, 2025)
The Indian tasar silkworm Antheraea mylitta (A. mylitta) is an economically important silkmoth and is native to tropical India. Our current research has deciphered the mitochondrial genome (mitogenome) of A. mylitta by recovering the complete genome sequence from the NCBI-SRA database and comparing it with other mitogenomes from the order Lepidoptera. The mitogenome is a double-stranded circular molecule spanning 15,354 bp with an A + T content of roughly 80.4%. It consists of a total of 37 genes, comprising 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), and two ribosomal RNAs (rRNAs), along with a 337 bp long control region. The arrangement of PCGs is similar to other Lepidoptera mitogenomes, with the exception of Cox1 and Cox2, which have different initiation codons. The control region of A. mylitta contains a conserved five bp ATAGA motif as seen in other Antheraea species. Phylogenetic analysis supports previous morphological hypotheses that Bombycoidea, Noctuoidea, Geometroidea, Papilionoidea, and Torticoidea are monophyletic. The divergence time analysis of 13 protein-coding genes reported that A. mylitta diverged from the last common ancestor ∼ 23 million years ago. As per our knowledge, this is the first documented record of the entire mitogenome of A. mylitta.